The Values of Tholabul ‘Ilmi in the Story of Prophet Musa and Prophet Khidr (A Comparative Study of Tafsir Ibn Kathir and Ihya’ Ulumuddin) - Musaffa, Rifqi; Abidin, Zainal (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2025)
The decline in students’ moral quality in Indonesia—manifested in frequent brawls, weakened respect for teachers, and the erosion of educators’ authority as moral exemplars—highlights a systemic crisis in education, where cognitive goals often overshadow ethical and spiritual formation. This study addresses the central problem of how Islamic pedagogy, particularly the Qur’anic story of Prophet Musa and Khidr (QS. al-Kahf: 60–82), can offer solutions to this moral and educational challenge. Employing qualitative library research, the study conducts a comparative textual analysis of Tafsir Ibn Kathir and al-Ghazali’s Ihya’ ‘Ulum al-Din, supported by contemporary scholarship on Islamic education. The analysis reveals seven thematic dimensions of thalabul ‘ilmi: the divine nature of knowledge, teacher–student relational ethics, transformative learning through experiential challenges, patience as a pedagogical principle, integration of intellectual and spiritual growth, the temporary nature of mentorship, and the ultimate goal of divine proximity. Ibn Kathir underscores Musa’s perseverance and humility as models for sincere seekers of knowledge, while al-Ghazali emphasizes purification of the soul and moral integrity as prerequisites for meaningful learning. Both sources converge on the principle that authentic education transcends mere information transfer, requiring critical engagement, patience, and eventual learner independence. These findings resonate strongly with modern educational theories such as experiential learning, scaffolding, and transformative pedagogy, yet uniquely integrate spirituality as the central axis of formation. The study argues that the Musa–Khidr model provides a holistic pedagogical framework for contemporary Islamic institutions, bridging the divide between traditional memorization-based learning and secular analytical approaches. By prioritizing autonomy, resilience, and moral depth, this model offers educators practical guidance for curriculum design, teacher training, and institutional reform. Ultimately, the research demonstrates that Qur’anic narratives, when dialogued with classical scholarship, can contribute not only to the revitalization of Islamic education but also to global educational discourse by uniting intellectual rigor with ethical and spiritual development. Keywords: Thalabul ‘Ilmi; Ibn Kathir; Ihya Ulumuddin; Musa–Khidr; Comparative Study